Propaedeutics in Practice: Islamic Legal Studies and the Public Sphere (American Journal of Islam and Society, 2020)
In this paper, I outline a propaedeutics of Islamic legal studies. I am using the term “propaedeutic” to refer to scholarship and pedagogy that introduces audiences to new material in a way that structures their curiosities and asks them to rethink commonplace familiar situations and assumptions. Those who teach about Islamic law in North American Islamic studies are working in an environment shaped by distinctive anxieties and preconceptions. Engaged scholarship informed by thinkers such as Wael Hallaq and Talal Asad seeks to disentangle conceptions of law from modern expectations of law enforcement, codification, and the supervisory neutrality of the state to consider other deliberations and practices of justice. Such propaedeutic scholarship should suggest how religious legal authority deals with more than just “spiritual” and “personal” matters. Imprecise introduction to the idea that Islamic legal opinion is non-binding can unintentionally imply that such opinion makes only moral suggestion that one chooses to follow or not. Scholarscritical of Max Weber’s judgment that Islamic jurisprudence amounts to little more than arbitrary invocations of authority should be careful not to present Islamic jurists as merely creatively “free” to be unsystematic and their decisions inconsequential if following them is not coerced. Drawing on the work of Hussein Agrama, I explore the idea of fatwa discernment as guiding counsel directed not at adversarial procedure but at ethical self-formation. Finally, I consider Saba Mahmood’s account of religious difference to suggest how Islamic legal traditions might complicate liberal ideas of jurisdiction.